The Relationship Between Prayer Intensity and Family Support with Post Surgery Pain - Mulyadi, Mulyadi; Ediyono, Suryo (Jurnal MIDPRO, 2023)
Post operative pain is still a major problem for patients after surgery. Management of pain is still focus on the sensory component. The aims of this research was to explain the intensity of prayer and family support correlated with post operative pain. Analytic correlational was the method of this research. Samples were 40 patients admitted with chronic appendicitis at Nashrul Ummah Islamic Hospital and were found by Total sampling. Analysis of data bivariate test using pearson product moment and multivariate analysis using logistic regression with p significance < 0.05. There is a significant and negative correlation between intensity of praying with post operative pain (p = 0,000; r=-0,914) and also between family support with the post operative pain (p = 0.000; r= 0.704). Jointly a significant relationship exists between the intensity of prayer and family support with the post-operative pain, with values as a correlation coefficient (R) = 0.923, a determinant coefficient (R 2 = 0.852), F regression = 77.772, p = 0.000. The intensity of praying greater impact than the family support against the post-operative pain. The result effective contribution of intensity praying to post-operative pain is 73.1%, meanwhile, the effective contribution of family support is 14%. There is a negative correlation between the intensity's praying and the family support with the post operative pain. tThe intensity of praying is greater impact than the family support.